Evaluation issues in the Swedish Two-County Trial of breast cancer screening: An historical review. (March 2017) - Tabar, Laszlo; Chen, Tony Hsiu-Hsi; Hsu, Chen-Yang; Wu, Wendy Yi-Ying; Yen, Amy Ming-Fang; Chen, Sam Li-Sheng; Chiu, Sherry Yueh-Hsia; Fann, Jean Ching-Yuan; Beckmann, Kerri; Smith, Robert A; Duffy, Stephen W
Objectives: To summarize debate and research in the Swedish Two-County Trial of mammographic screening on key issues of trial design, endpoint evaluation, and overdiagnosis, and from these to infer promising directions for the future. Methods: A cluster-randomized controlled trial of the offer of breast cancer screening in Sweden, with a single screen of the control group at the end of the screening phase forms the setting for a historical review of investigations and debate on issues of design, analysis, and interpretation of results of the trial. Results: There has been considerable commentary on the closure screen of the control group, ascertainment of cause of death, and cluster randomization. The issues raised were researched in detail and the main questions answered in publications between 1989 and 2003. Overdiagnosis issues still remain, but methods of estimation taking full account of lead time and of non-screening influences on incidence (taking place mainly before 2005) suggest that it is a minor phenomenon. Conclusion: Despite resolution of issues relating to this trial in peer-reviewed publications dating from years, or even decades ago, issues that already have been addressed continue to be raised. We suggest that it would be more profitable to concentrate efforts on current research issues in breast cancer diagnosis, treatment, and prevention.